Um caso de transposição didática dos gêneros textuais: a Nova Proposta Curricular do Estado de São Paulo e os Cadernos do Aluno do Ensino Médio - Jacob, Ana Elisa (2013)
This research aims to evaluate the proposed didactic transposition of text genres by the Secretaria de Estado da Educação de São Paulo (SEESP), from the year 2008 to implement the New Curriculum Proposal. More specifically, analyzing the texts of curriculum guidance and educational materials produced by that institution as the genders were transposed from its conceptualization to the didactic treatment. We believe that this research is embedded within two major issues that are closely linked: the teaching of textual genres in Brazil, which conceptual consensus of the scientific field as both didactic unclear, difficult to understand and their appropriation by those involved in the educational process, and the political and economic influences in the selection of objects and teaching methodologies adopted that, throughout the national education history faced as a true marketing tool, and take the teaching and learning tools (teaching materials) as sufficient to improve quality of the education offered. We seek, therefore, through the theoretical contributions on the Didactic Transposition (transformations that knowledge and social practices suffer to become teachable), developed primarily by Chevallard (1991), we understand the possible transformations that knowledge can be by being communicated to suffer through texts , so not believing in a vision applicationist of knowledge, but in the dialectic context and intertext influence and shape it. After understanding such transpositional (or transformational) movements resorted to studies textbooks Genevans, interactionist Sociodiscursivos (ISD), who propose a didactic transposition consistent with the needs of the local community, the capabilities already developed by students and those that the school determines how important they are developed. These studies provide a basis in addition to psychological and discursive processes that explain how to provide material and symbolic development in and through language, also gives us the support for the analysis of teaching materials through its own analysis methodology texts ISD (Bronckart, 1999 ) and the concepts elaborated on Models of Teaching (DE PIETRO, 1996/1997) (Schneuwly & Dolz, 1997) - descriptive and operational object that gives us conditions to apprehend the complex phenomenon of learning a genre - Sequences and Teaching (Dolz, NOVERRAZ & Schneuwly, 2001) - systematic teaching of a knowledge that enables the teacher and the student to take ownership of their size teachable - which are widely disseminated and adopted didactic proposals both in Brazil and abroad. The Methodological Procedure used to achieve our goals, consisted primarily in reviewing plans and declarative semantics of the Curriculum Proposal SEESP, to know what the conceptions of language and learning adopted are, and certain educational goals and referrals for treatment of object of teaching. Then we analyze the dimensions of teachable text genres worked in didactic activities, classifying them according to the three language skills (action, discursive and linguistic-discursive), thus to understand how the didactic was and hence the transformations typical of the process of didactic transposition. The results obtained with this procedure was that the concept of genre was not discussed in the text of the New Curriculum Proposal, hindering thus the understanding of its main targets, teachers, teaching the object itself. Regarding the teaching of genres proposed, did not contemplate the purpose and referrals textbooks prescribed at first, and not the teachable dimensions work progressively along the series of High School, presenting problems in the process of didactic transposition